Therapeutic Inertia in the Management of Psoriasis: A Quantitative Survey Among Indian Dermatologists and Patients - Rajagopalan M; Dogra S; Godse K; Kar BR; Kotla SK; Neema S; Saraswat A; Shah SD; Madnani N; Sardesai V; Sekhri R; Varma S; et al. (Dove Medical Press, 2022)
Murlidhar Rajagopalan,1 Sunil Dogra,2 Kiran Godse,3 Bikash Ranjan Kar,4 Sai Krishna Kotla,5 Shekhar Neema,6 Abir Saraswat,7 Swapnil Deepak Shah,8 Nina Madnani,9,10 Vidyadhar Sardesai,11 Rajiv Sekhri,12 Sachin Varma,13 Sandeep Arora,14 Pallavi Kawatra15 1Department of Dermatology, Apollo Hospital, Chennai, India; 2Department of Dermatology Venereology & Leprology Postgraduate Institute of Medical Education & Research (PGIMER), Chandigarh, 160012, India; 3DY Patil University School of Medicine, Navi Mumbai, India; 4Department of Dermatology, IMS and SUM Hospital, Bhubaneshwar, Odisha, India; 5Department of Dermatology, Yashodha Hospital, Secunderabad, India; 6Department of Dermatology, Armed Forces Medical College, Pune, Maharashtra, India; 7Indushree Skin Clinic, Lucknow, India; 8Department of Dermatology, Ashwini Rural Medical College, Solapur, India; 9Hinduja Hospital, Mumbai, India; 10Sir. H. N. Reliance Hospital, Mumbai, India; 11Bharati Vidyapeeth Medical College, Pune, India; 12Fortis Hospital, Noida, India; 13Skinvita Clinic, Kolkata, West Bengal, India; 14Army College of Medical Sciences, New Delhi, India; 15Novartis, Mumbai, IndiaCorrespondence: Murlidhar Rajagopalan, Department of Dermatology, Apollo Hospital, Chennai, India, Email docmurli@gmail.comPurpose: The primary objective of the study was to understand the therapeutic inertia in treatment and management of plaque psoriasis among dermatologists, along with determining the preferred treatment choices for management of plaque psoriasis; it also included the resulting treatment satisfaction among patients. The secondary objective was to identify the gaps in terms of knowledge and attitude among dermatologists and the expectations of patients.Patients and Methods: A multicentre, cross-sectional quantitative survey was conducted among dermatologists and patients with moderate to severe plaque psoriasis across India. The interviews were conducted either face to face or via telephone between September and November 2020, using structured and validated questionnaires based on specific themes. The data obtained were statistically analysed, wherever applicable.Results: Overall, 207 adult patients with moderate-to-severe plaque psoriasis and 303 dermatologists were interviewed. Post experiencing symptoms, 44% of the patients visited general physicians for treatment and there was an average 7.8-month delay by the patients to consult a dermatologist. Approximately one-fourth of patients used home remedies before seeking medical help. One-third of dermatologists used the Psoriasis Area and Severity Index (PASI) for assessing the disease severity. Majority of dermatologists preferred combination therapy for their patients. The lack of quick resolution and side effects were the major reasons for changing the treatment. Overall, only 35% of the patients complied to current treatment. Satisfaction with existing forms of therapies was highest for mild plaque psoriasis (62%) as confirmed by dermatologists, while 52% of the overall patients were satisfied with their therapy. Majority of the patients (64%) affirmed living with plaque psoriasis impacted their lives.Conclusion: This first-of-its-kind survey in India highlighted the gaps in terms of the disease journey between dermatologists and patients. The survey emphasises the need for shared decision-making and may benefit dermatologists in suggestive modifications of the treatment algorithm and disease management in clinical settings.Keywords: therapeutic inertia, psoriasis, adherence, treatment expectations, treatment goals, diagnosis